PENGARUH VARIASI PARAMETER PROSES PEMBUBUTAN TERHADAP KEKASARAN PERMUKAAN PADA MATERIAL S45C - Muhammad Reza Mukhib; Eko Yudo; Muhammad Haritsah Amrullah (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Lathes include one type of tooling machine, the working principle in the lathe process is the process of removing parts of the workpiece. The purpose of the study was to determine the effect of spindle rotation, dietary depth, and cooling media variations (Oli, dromus, air). The process of subsubsting uses the MAWItec D.O.O lathe.B 160x1000, and uses S45C material. This study uses the RSM method. Minimal research results in this study with variations in parameters spindle rotation 1000 RPM (factor 1 level 3), nutritional depth 0.7 (factor 2 level 2) and air conditioning media (3) (factor 3 level 3) with a resulting roughness value of 1,662 μm.